Swimming Upstream, Floating Downstream: Comparing Women's Relative Wage Position in the U.S. and Denmark - Nabanita Datta Gupta; Ronald L. Oaxaca; Nina Smith (Institute for the Study of Labor (IZA), 2003)
We compare how U.S. and Danish gender wage gaps have developed between 1983 and 1995 using U.S. PSID and Danish Longitudinal Sample data. Using a new decomposition method, we show that changes in returns to observable skills and ranking effects outweigh women?s gains due to qualifications and account for a rising gap in Denmark, while these effects cannot counter the large decline in the wage gap in the U.S. in this period. Increased wage dispersion has a minimal effect on the gap in both countries. Women at the highest decile in Denmark face the biggest increase in the gap, while in the U.S., the decline is largest at the top and at the middle of the distribution.
Keywords: J7; 330; gender wage gaps; decomposition method; Lohndifferenzierung; Geschlecht; Vergleich; Vereinigte Staaten; Dänemark